ASME 2012 Internal Combustion Engine Division Spring Technical Conference 2012
DOI: 10.1115/ices2012-81232
|View full text |Cite
|
Sign up to set email alerts
|

Large Particles in Modern Diesel Engine Exhaust

Abstract: During research on diesel engine EGR cooler fouling a test stand giving visual access to the building deposit layer has been developed. Initial experiments reveal the presence of large particles in the exhaust. While conventional wisdom is that diesel particulates typically have log-normal size distributions ranging approximately 10–200 nm, the tests reported here observe small numbers of particles with sizes on the order of tens of μm. Such particles are not generally reported in the literature because exhaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The latter value falls well within the range between 40 nm to 80 nm reported previously (Harris and Maricq, 2001). Some studies have also reported diesel soot aggregates significantly larger than 200 nm diameter, even reaching supermicron sizes (Hoard et al, 2013). Such particles likely result from flaking particle deposits that build up within the combustion chamber or the exhaust pipe.…”
Section: Soot Aggregate Size and Compactionsupporting
confidence: 87%
“…The latter value falls well within the range between 40 nm to 80 nm reported previously (Harris and Maricq, 2001). Some studies have also reported diesel soot aggregates significantly larger than 200 nm diameter, even reaching supermicron sizes (Hoard et al, 2013). Such particles likely result from flaking particle deposits that build up within the combustion chamber or the exhaust pipe.…”
Section: Soot Aggregate Size and Compactionsupporting
confidence: 87%
“…Only at temperatures of around 230 K, where the homogeneous ice nucleation rate may be critical, can the stochastic nature of ice nucleation be relevant. Therefore, vertical velocity, which is a determining factor for the number of homogeneously nucleated ice crystals (Hoyle et al, 2005;Kärcher and Lohmann, 2002;Sullivan et al, 2016), does not influence the number of ice crystals nucleated through soot PCF and can be neglected in the soot-PCF framework. It should further be noted that the function P N (RH) can either be used to bring AF(RH) into agreement with an experimental dataset or be derived from soot properties by inspecting the different onset RH required to nucleate and grow ice out of ring pores, as shown in Appendix D. Note that within aggregates, there may be structures that are not fully closed to form ring pores.…”
Section: B2 Slit Filling Between Two Adjacent Primary Particles With Liquid Watermentioning
confidence: 99%
“…These particles may be flakes of deposits from the cylinder or exhaust system, and are not normally measured by typical particulate measuring instruments. We hypothesize that small flakes discussed above were also caused by these big particles that are not in the range of exhaust soot particles usually reported in literature (Hoard et al, 2012). Therefore, we studied the existence of big particles in the exhaust stream.…”
Section: Deposition Testsmentioning
confidence: 92%